Los Estados De Afecto Positivo Y Afecto Negativo Como Variables Explicativas De La Ansiedad Escénica En Estudiantes De Magisterio - Zarza-Alzugaray, Francisco Javier; Bustamante, Juan Carlos; Casanova, Oscar; Orejudo, Santos (European Scientific Journal, ESJ, 2016)
In the students of Primary Education Teaching we see how music performance anxiety proves to be one of the key problems for the overcoming of subjects related to musical study and practice. Thus we see how this problem is related to personal characteristics such as general anxiety, either trait or state, self-perceived musical competence or affects, either positive or negative, both trait and state. In this study we sought to analyse the predictive value that these variables have on the levels of the performance anxiety experienced. The results show how half of the students participating in the study show higher levels of performance anxiety than the theoretical mean of the measuring instrument used and how this construct is significantly related to general anxiety, self-perceived musical ability and affect. It has also been shown how, in order to explain the greater or lesser presence of music performance anxiety, both positive and negative affect in their state measure are those with greater explanatory capacity. More research is needed in order to create specific training programs that help students to generate regulatory adaptive mechanisms that help to better focus the music performance during the evaluative processes of this type of subjects.